The Role of Land Use Conversion in Shaping the Land Cover of the Central American Dry Corridor - Gotlieb, Yosef (2020)
The Central American Dry Corridor (CADC) is a trans-border region characterized by climatic and ecological continuities. It is expected to experience rising aridity and severe hydro-climatic events due to climate change. Subsistence agriculture and other rural livelihoods to which land cover is central are widely practiced in this impoverished territory of approximately eleven million people. The CADC’s land cover was profiled to determine: a) how it differs from Non-CADC areas, and b) the role of land use in shaping these differences. Spatial autocorrelation analysis using satellite data showed that forest cover is a third less prevalent in the CADC than in the Non-CADC while the share of mosaic vegetation and mosaic cropland is nearly double. A naturally prevalent cover type in the CADC, tropical dry forest (TDF), has been largely eliminated. The significantly lesser proportion of forest and greater percentage of coverage consistent with agriculture and ranching implicate land use conversion, specifically deforestation for agricultural expansion and cattle ranching, in shaping CADC land coverage. The process began in the mid-1800s when small-scale agriculturalists migrated to the region followed by large-scale export crop and beef production, primarily for international markets. Deforestation peaked after WWII, concluding by the 1990s with the conversion of most woodlands. Similar patterns now threaten forests along the Caribbean coast. Traditional land use practices cannot sustain local communities or preserve the resource base, thereby contributing to rural outmigration. Adopting sustainable practices and promoting livelihoods strategies leading to forest regeneration will be fundamental for CC adaptation in the CADC.